2010
DOI: 10.1039/c002454f
|View full text |Cite
|
Sign up to set email alerts
|

A novel and efficient methodology for the construction of quinazolines based on supported copper oxide nanoparticles

Abstract: A series of quinazolines were synthesized from 2-aminobenzophenones and benzylic amines in good to excellent yields by employing a new heterogeneous catalyst based on the copper oxide nanoparticles supported on kaolin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(44 citation statements)
references
References 34 publications
1
43
0
Order By: Relevance
“…Although this method is efficient, it has limited substrate scope with few examples. Wang and coworkers [34] synthesized various quinazolines from 2-aminocarbonyl compounds and benzyl amines as starting materials using CuO nanoparticles supported on kaolin. The same research group reported quinazoline synthesis using I2/TBHP as another catalytic system [35].…”
Section: Introductionmentioning
confidence: 99%
“…Although this method is efficient, it has limited substrate scope with few examples. Wang and coworkers [34] synthesized various quinazolines from 2-aminocarbonyl compounds and benzyl amines as starting materials using CuO nanoparticles supported on kaolin. The same research group reported quinazoline synthesis using I2/TBHP as another catalytic system [35].…”
Section: Introductionmentioning
confidence: 99%
“…White solid; yield: 87%; mp: 196–198°C (lit. 190–192°C) ; IR (neat, cm −1 ): 3051, 1556, 1530, 1473, 1381, 1301, 1157, 1071; 1 H‐NMR (500 MHz, CDCl 3 ) δ: 7.49–7.55 (m, 3H), 7.60–7.64 (m, 3H), 7.81(dd, 1H, J 1 = 2 Hz, J 2 = 9 Hz), 7.85–7.88 (m, 2H), 8.09–8.11 (m, 2H), 8.66–8.68 (m, 2H); 13 C‐NMR(100.6 MHz, CDCl 3 ) δ: 122.2, 125.8, 128.6, 128.7, 128.8, 130.1, 130.2, 130.8, 130.9, 132.6, 134.5, 137.1, 137.8, 150.5, 160.5, 167.6; ESI MS ( m / z ) = 317.1 (M + H) + ; Anal . Calcd for C 20 H 13 ClN 2 : C, 75.83; H, 4.14; N, 8.84, Found: C, 75.67; H, 4.28; N, 8.71.…”
Section: Methodsmentioning
confidence: 99%
“…Usually, the traditional synthesis of quinazolines involves reactions of Bischler cyclization, dicarbonyl compounds with diamines and reactions from 2-aminobenzonitriles or anthranilic acids as well as N-arylbenzamides [6][7][8][9]. Our group have been focusing in the synthesis of quinazolines and a variety of excellent approaches to the quinazolines were developed [10][11][12][13]. At the same time, other groups also developed some novel methods to prepare these quinazoline derivatives [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 97%